Global Hindu diaspora
1 online resource (235 pages)
Keywords: "This book examines Hinduism from both a historical and contemporary perspective. It provides some interesting insights into factors that shaped and defined Hinduism in the diaspora. It also examines the challenges facing Hinduism in the twenty-first century. In recent years the growing conversions of Hindus to other religions, the complexities of caste, the impact of AIDS, and the need to reinvigorate the youth in Hindu teachings are just some of the issues that it faces. What shape and form will Hinduism take in the twenty-first century? What will Hinduism look like in the future? These relevant questions are the subject of debate and deliberations amongst religious scholars, academics and politicians. This edited collection addresses some of these questions as well as the relationship between religion and diaspora within historical and contemporary perspectives."--Provided by publisher.